Relationship between Prolonged QT Interval and Mortality in COVID-19 Patients at Ulin Hospital, Banjarmasin - Djallalluddin, Djallalluddin; Prenggono, Muhammad Darwin; Fajari, Nanang Miftah; Rudiansyah, Mohammad; Elfa, Loudry (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: QT prolongation in COVID-19 infection may be caused by SARS-CoV-2 infection, inflammation, ischemia, hypoxia, and the administration of drugs related to COVID-19. This condition is associated with a poor prognosis due to an increased risk of ventricular arrhythmias and sudden cardiac arrest. METHODS: This study used an observational case-control design. Data were obtained consecutively using medical records of COVID-19 patients confirmed through RT-PCR swabs who died (case) and survived (control) at Ulin General Hospital, Banjarmasin. The number of samples in this study was 138 patients. The independent variables were prolonged QT interval (>430 m/s or QTc >450 m/s) and normal QT interval, while the dependent variable was the mortality of COVID-19 patients. RESULTS: QT prolongation significantly increased the risk of death by 4 times (OR 4.48; 95% CI = 2.162-9.280; p = 0.000) compared to COVID-19 patients with normal QT intervals. DISCUSSION: Prolonged QT intervals increased the risk of death in COVID-19 patients at Ulin General Hospital, Banjarmasin. These findings are in accordance with several other studies where this variable might be used as a prognostic factor in the mortality of hospitalized COVID-19 patients. CONCLUSION: Prolonged QT intervals are associated with mortality in patients with COVID-19 at Ulin Hospital, Banjarmasin.